Training education of digital media to develop of Pasar Yosomulyo Payungi - Suhono Suhono; Mai Zuniati; Dharma Setyawan; Umar Al Faruq A Hasyim; Wiwied Pratiwi; Dian Anggraini; Moh Dimyati; Haikal Haikal (Universitas Sarjanawiyata Tamansiswa, 2023)
The aim of this article is the assistance of education training in digital media to increase skills in the management of traditional snack promotions through Instagram, fan pages, and graphic design to impact financial markets' income or profitability for the community at Payungi (Pasar Yosomulyo Payungi). The researchers used ABCD (Asset Based Community) Method to maximize the potential assets, which includes individual assets, communities, infrastructure, and community. The result showed that the economy of the residents around Payungi was assisted and impacted new jobs and good relationships among stakeholders. The economy of the people around Payungi is helped, new jobs appear, and the relationships built within them support each other. They no longer need each other but are mutually beneficial. Other results show that the community can access information from competent sources, the audience gets interesting material, the resource persons get an instant and massive audience, and traders have greater opportunities because buyers gather in one location.